1992
DOI: 10.1159/000196097
|View full text |Cite
|
Sign up to set email alerts
|

Local Immune Components in Chronic Obstructive Pulmonary Disease

Abstract: Bronchoalveolar lavage (BAL) may have a potential role in contributing to a more precise definition of COPD disorders, but at present little is known about the cellular and biochemical changes that occur in BAL in the different stages of COPD. On the contrary, BAL features due to smoking habits, a well-known risk factor for COPD, have been widely investigated. We submitted to BAL 15 normal nonsmokers, 15 asymptomatic smokers and 11 smokers affected by chronic bronchitis. In this latter group BAL fluid recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionmentioning
confidence: 85%
“…The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionmentioning
confidence: 85%
“…There is good evidence for limited protein oxidation during inflammatory reactions ; for example, broncheoalveolar fluids have elevated methionine sulphoxide\methionine ratios under conditions in which leucocyte activation is apparent [221]. Furthermore, oxidized proteins (and DNA) form inside the leucocytes during their triggering, as judged by protein carbonyls [222] and tyrosine modification [223], although it is not clear whether this affects protein function directly.…”
Section: Protein Oxidation In Host Defence and Tissue Catabolismmentioning
confidence: 99%
“…1 For many years, the main focus of interest has been neutrophils and macrophages, but more recent pathologic and bronchoalveolar lavage (BAL) studies have suggested an important role of CD8 1 T cells in the development of COPD. [2][3][4][5] CD4 1 T lymphocytes are subclassified into T H 1 and T H 2 cells. T H 1 cells produce IFN-g, IL-2, and TNF in the absence of IL-4, IL-5, IL-9, and IL-13.…”
mentioning
confidence: 99%